Recovery at Work: Understanding the Restorative Side of “Depleting” Client Interactions - Lilius, Jacoba M. (Academy of Management Review, 2012)
Research on burnout has considered client interactions solely as depleting, with work recovery possible only while employees are off the job. Drawing on an episodic perspective of work, I argue that there is unaccounted for variability in the nature of a caregiver's client interactions such that some are actually restorative rather than depleting. I outline the foundations of such variability through simultaneous consideration of the extent to which a given interaction is (1) depleting of regulatory resources and (2) generative of three particular resources shown to compensate for the effects of ego depletion. Beyond the depleting interactions that have been the focus of research to date, the resulting typology reveals two restorative interaction types (replenishing and breakthrough) that I theorize positively shape compassionate care provision in both the short and long term. Replenishing interactions primarily serve as a regulatory break with momentary effects on caregivers' subsequent ability to self-regulate, while breakthrough interactions have a more lasting effect on caregivers' positive professional identity. This framework articulates how restorative experiences may be concurrent with the accomplishment of work and provides a more nuanced alternative to the long-held view of client interactions as a source of caregiver depletion.